Pengembangan Media Scrapbook Berbasis Qr Code Negara-Negara Asean Pada Kelas VI Tema 8 Subtema 1 SDN Kamal 2 - Riska Aulia; Parrisca Indra Perdana (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The purpose of this study was to develop a valid, effective and attractive QR Code-based scrapbook media for ASEAN countries in class VI theme 8 Sub-theme 1. The subjects of this study were 6 students in class VI in small group trials and 15 students in large group trials. By using data collection techniques, namely interviews, observations, questionnaires and test sheets. The results showed that: 1) the average validity of the expert validator was 86.41%, 2) the results of the effectiveness trial were obtained from the teacher activity observation sheet obtaining a percentage of 92.18% and 90.59% from the small group trial results and large groups, student activity observation sheets obtain percentages of 91.27% and 88.64% from the results of small group and large group trials, and student classical learning outcomes obtain percentages of 100% , 3) the results of the attractiveness test are obtained from the results of the teacher's response 95 % and 92.5% of the results of the small group and large group trials and the results of student responses 92.91% and 93.66% of the results of the small group and large group trials. Based on the results of the research, the QR Code-based scrapbook media for ASEAN countries shows very valid, very effective and very interesting criteria so that it can be used in theme 8 sub-theme 1 learning 3 and 4 class VI.